'We don't have anything': understanding the interaction between pastoralism and terrorism in Nigeria. Issue 4 (4th July 2022) - Ejiofor, Promise Frank
ABSTRACT: Since 2011, the Sahel has been bedevilled by insecurity spawned by communal strife, social fragmentation, and religious extremism. Some of the security conundrums in the region are perpetrated by some pastoralists who have turned criminals and established strong ties with terrorist groups such as Jama'at Nusrat al-Islam wal-Muslimin (JNIM), Islamic State in the Greater Sahara (ISGS), Islamic State West Africa Province (ISWAP), and Boko Haram. Whilst the reasons for the emergence of militant jihadism have been largely explored in the vast corpus on terrorism, less attention has been devoted to understanding-cum-explaining the reasons pastoralists take up arms and join terrorist groups. The few scholarly publications on the problematic posit that the reasons for pastoralists' resort to terrorism in the region lie in political ecology and pastoralist populism. In this article, I contend that these dominant explanations sidestep the socioeconomic context within which pastoralists struggle to eke out a bare existence as well as the varied everyday abuses perpetrated by state and non-state actors against pastoralists. Drawing on the relative deprivation conceptual framework advanced by the American political scientist Ted Gurr, I argue that pastoralists join terrorist groups because they perceive discrepancies between their past and present socioeconomic condition but also as a consequence of marginalisation and everyday abuses against pastoralists. I illustrate the pastoralism-terrorism nexus with the crucial case of Nigeria―Africa's most populous state and largest economy.